Redistribution of the astrocyte phenotypes in the medial vestibular nuclei after unilateral labyrinthectomy - Li, Jie; Wang, Pengjun; Wang, Lu-Yang; Wu, Yaqin; Wang, Jiping; Yu, Dongzhen; Chen, Zhengnong; Shi, Haibo; Yin, Shankai (Frontiers in Neuroscience, 2023)
Astrocytes are highly heterogeneous and involved in different aspects of fundamental functions in the central nervous system (CNS). However, whether and how this heterogeneous population of cells reacts to the pathophysiological challenge is not well understood. To investigate the response status of astrocytes in the medial vestibular nucleus (MVN) after vestibular loss, we examined the subtypes of astrocytes in MVN using single-cell sequencing technology in a unilateral labyrinthectomy mouse model. We discovered four subtypes of astrocytes in the MVN with each displaying unique gene expression profiles. After unilateral labyrinthectomy, the proportion of the astrocytic subtypes and their transcriptional features on the ipsilateral side of the MVN differ significantly from those on the contralateral side. With new markers to detect and classify the subtypes of astrocytes in the MVN, our findings implicate potential roles of the adaptive changes of astrocyte subtypes in the early vestibular compensation following peripheral vestibular damage to reverse behavioral deficits.